Legal Protection and Legal Certainty in Indonesia’s Land Title Registration System - Agung, Anak Agung Istri; Sukandia, I Nyoman; Puspadma, I Nyoman Alit; Chornous, Yuliia (JURNAL AKTA, 2022)
This research aims to scrutinize challenges in Indonesia’s land title registration system, focusing on legal protection and certainty for land title holders, particularly when titles are acquired through binding agreements. Emphasis is placed on publicity principle, exploring its role in ensuring transparent access to information about land titles. The normative legal research method, employing a normative juridical approach, involves a thorough examination of legal materials, including theories, concepts, and legislation such as Regulation Number 16 of 2021, Government Regulation Number 24 of 1997, and Government Regulation of the Republic of Indonesia Number 18 of 2021. Results highlight a significant gap between land title deeds based on agreements and the necessity for proper registration to guarantee legal protection. Failure to register undermines the “opernbaarheid” principle, turning agreements into private arrangements. Addressing this gap is crucial for establishing a transparent land title registration system, ensuring uniform legal protection for all holders, and reducing potential disputes. The implications of this research extend to policymakers, legal practitioners, and stakeholders, offering insights to enhance the transparency and effectiveness of Indonesia’s land administration. Policymakers can leverage these findings to refine regulations, aligning the system with principles of openness and accessibility, fostering a fair land tenure system, and supporting sustainable development.